Dampak Obyek Wisata Pantai Jikomalamo terhadap Kehidupan Sosial Ekonomi Masyarakat (Suatu Studi Antropologi Pariwisata ) - Dewi Apriani Aco (Universitas Khairun, 2018)
The impact to tourism is negative if it courses change that is not desirable or detrimental to the culture of the local community, otherwise, the impact of tourism is considered positive if it is able to provide benefits, for the people economics well fare, revitalization and conversation for the existence of the local culture. community and environmental preservation the development of awell carried out tourist attraction and economic income which is else good for local communication.a place that well planned not only provides economic benefits. Which improves that level of quality and lifestyle of the local community.but also changes and maintains a better environment. Keyword: Tourism, impact, society